2020
DOI: 10.1002/yea.3532
|View full text |Cite
|
Sign up to set email alerts
|

Giant GAL gene clusters for the melibiose‐galactose pathway in Torulaspora

Abstract: In many yeast species, the three genes at the centre of the galactose catabolism pathway, GAL1, GAL10 and GAL7, are neighbours in the genome and form a metabolic gene cluster. We report here that some yeast strains in the genus Torulaspora have much larger GAL clusters that include genes for melibiase (MEL1), galactose permease (GAL2), glucose transporter (HGT1), phosphoglucomutase (PGM1) and the transcription factor GAL4, in addition to GAL1, GAL10, and GAL7. Together, these eight genes encode almost all the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Given previous indications gathered in earlier stages of this study, we analysed in more detail the genes implicated in galactose and maltose metabolism. It was recently reported that species of Torulaspora have large clusters of genes necessary for galactose metabolization (Venkatesh et al, 2020). These clusters have the GAL 7 ‐ 1 ‐ 10 ‐ 4 and the GAL 7 ‐ 1 ‐ 10 ‐ 2 configuration (other genes, such as HGT1 , MEL1 and PGM1 , are also part of the GAL cluster).…”
Section: Resultsmentioning
confidence: 99%
“…Given previous indications gathered in earlier stages of this study, we analysed in more detail the genes implicated in galactose and maltose metabolism. It was recently reported that species of Torulaspora have large clusters of genes necessary for galactose metabolization (Venkatesh et al, 2020). These clusters have the GAL 7 ‐ 1 ‐ 10 ‐ 4 and the GAL 7 ‐ 1 ‐ 10 ‐ 2 configuration (other genes, such as HGT1 , MEL1 and PGM1 , are also part of the GAL cluster).…”
Section: Resultsmentioning
confidence: 99%
“…A series of genes related to growth and reproduction were also up-regulated in PATinduced M. guilliermondii. The gene mel1 is a metabolism-associated gene that encodes α-galactosidase, a key enzyme in the catabolic pathway of galactose and glucose disaccharide [30], and the gene ETR1 that encodes enoyl reductase is associated with yeast fatty acid synthesis (fatty acid synthesis type II) and respiratory metabolism [31]. The flavodoxin-like genes YCP4 regulate the expression of several metabolism-related genes during the late growth stage of yeast [32].…”
Section: Discussionmentioning
confidence: 99%
“…As in other eukaryotes, the chromosomal location of most genes in budding yeasts seems to be arbitrary and unrelated to their function or other properties [ 76 ]. Only a few examples of non-random gene locations are known, such as the metabolic clusters of GAL and DAL genes [ 77 , 78 ]. A few gene families such as the MAL and COS genes are specific to subtelomeric regions [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%